The influence of flowrate and gas density on positive airway pressure for high flow nasal cannula applied to infant airway replicas. (9th November 2020) - Moore, Charles; Rebstock, Douglas; Katz, Ira M.; Noga, Michelle L.; Caillibotte, Georges; Finlay, Warren H.; Martin, Andrew R.
Abstract: High flow nasal cannula (HFNC) therapy has been previously shown to produce positive upper airway pressures in adult and child patients. This work aimed to evaluate and quantify the effects of HFNC flowrate and gas type on airway pressures measured in vitro in infant airway replicas. Ten realistic infant airway replicas, extending from nares to trachea, were connected in turn to a lung simulator and were supplied gas flows through HFNC. Air and heliox were each provided at two weight-indexed flowrates, 1 l/min/kg and 2 l/min/kg. Pressure and lung volume were continuously measured during simulated breathing. For constant simulated patient effort, no statistically significant change in tidal volume was measured between baseline and lower or higher HFNC flowrates, nor was there any significant difference in tidal volume between air and heliox. Tracheal pressure increased with increasing HFNC flow rate, and was highly variable between airway replicas. Higher pressures were measured for air versus heliox. For air supplied at 2 l/min/kg, average airway pressures in excess of 4 cm H2 O were generated, with positive end-expiratory pressure (PEEP) ranging from 2.5 to nearly 12 cm H2 O across the replicas. A predictive correlation for PEEP was proposed based on supplied gas density and flow velocities exiting the cannula and nares, and was able to account for a portion of variability between airway replicas (R 2  = 0.913). Additionally, PEEP was well correlated with, and predictive of, expiratory peak pressure (R 2  = 0.939) and average inspiratory pressure (R 2  = 0.944).